Rent control law and its effect on property tax in India - Datta, Abyhijit (2002)
The paper addresses the public concern regarding the colateral impact of the rent control laws on valuation for property tax. It examines the legal aspects of the linkage between rent control and property tax in India within the board context of property tax reform. A detailed discussion of the various legislative attempts and suggested methods on presumptive determination of the mandated annual rental value follows. The paper concludes by noting that the judiciary has now recognized, twenty years later, that an insertion in the municipal law of a non-obstantate clause would ensure that the rent control laws do not influence municipal assessment of rental value. - Reproduced.
Keywords: Right to property - India; Right to property